Molecular identification and transmission mode of a phytoplasma and its effect on fatty acid composition in Taverniera cuneifolia. (April 2021) - Hemmati, Chamran; Nikooei, Mehrnoosh; Tahmasebi, Aminallah; Al-Sadi, Abdullah M.
Abstract: Taverniera cuneifolia plants showing shoots proliferation and witches' broom symptoms were observed in Minab, Iran. A study was performed to detect and identify the possible phytoplasma associated with the disease, identify the putative insect vector and possible modification in fatty acid composition of symptomatic plant roots. Sequence analysis revealed that the associated phytoplasma shared 99.92% sequence identity with ' Candidatus Phytoplasma australasia'-related strains. Successful transmission of phytoplasma by Orosius albicinctus to healthy periwinkle demonstrated its putative vector status. Moreover, analysis of the oil composition of the plant roots revealed an increased rate of fatty acid composition in the infected plants. Highlights: Molecular characterization of the phytoplasma associated with Taverniera cuneifolia witches' broom (TcWB) disease. Identification of Orosius albicinctus leafhopper as vector of the TcWB associated phytoplasma. Phytoplasma presence increases the concentration of unsaturated fatty acid composition in T. cuneifolia. Increase of unsaturated fatty acids/saturated fatty acids from 2.77 in symptomatic plants to 1.06 in asymptomatic ones.